The withdrawal of nutrition and hydration in the vegetative state patient: Societal dimension and issues at stake for the medical profession - Gigli, Gian Luigi; Valente, Mariarosaria (NeuroRehabilitation (Reading, Mass.), 2004)
The withdrawal of assisted nutrition and hydration (ANH) is increasingly supported by scientific societies, by hospitals and by some families, once the condition of vegetative state could be considered permanent. In the first part of this article, the authors present the factors used to support the decision to withdraw ANH: a) the prognostic evaluation about outcome transformed into a clinical diagnosis of permanency; b) basic health care transformed into a medical treatment, subject to refusal by the patient; c) the human life (an undisposable good) transformed into a disposable one, open to decisions made by surrogates; d) the evaluations about quality of life transformed into judgments about the indignity of human life to be lived. In the second part, the authors outline the changes that this attitude can provoke in the integrity and the juridical status of the medical and nursing professions, and its potential impact on the society at large.